2019
DOI: 10.3390/en12244639
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility between C6F12O–N2 Gas Mixture and Metal Used in Medium-Voltage Switchgears

Abstract: C6F12O has been introduced as the potential alternative gas to SF6 because of its excellent insulation properties and great eco-friendly performance. Considering that C6F12O may react with the internal materials of switchgears in practical applications, its compatibility with metal materials must be tested to evaluate its long-term application possibilities. In this work, the compatibility of C6F12O–N2 gas mixtures with aluminum and copper was tested at different temperatures by setting up a heat-aging reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It was found that corrosion of the copper surface gradually deepened as the interface temperature increased from 80 • C to 250 • C, while the aluminum surface remained stable. C 3 F 6 and C 3 F 7 H were produced during the interaction and the metal oxide crystal particles were precipitated on the copper surface [143] Severe corrosion also occurred on the copper surface [144,145].…”
Section: F 7 N Gas Mixturesmentioning
confidence: 99%
“…It was found that corrosion of the copper surface gradually deepened as the interface temperature increased from 80 • C to 250 • C, while the aluminum surface remained stable. C 3 F 6 and C 3 F 7 H were produced during the interaction and the metal oxide crystal particles were precipitated on the copper surface [143] Severe corrosion also occurred on the copper surface [144,145].…”
Section: F 7 N Gas Mixturesmentioning
confidence: 99%
“…C 2 F 6 exhibits a very high GWP of 9,200 CO 2 eq over 100 years, 16 as well as a remarkable atmospheric lifetime of 10,000 years, 15 as discussed at the beginning of this paper (Table 1). CF 4 and C 2 F 4 are considered two of the most harmful PFCs, due to their long lifetime.…”
Section: Stability At Short Time Periodsmentioning
confidence: 73%
“…5 Recent studies of HFO4E have shown a similar stability to SF 6 , presenting itself as an eco-friendly alternative to replace the already limited use of SF 6 in GIE. 24 In some of these studies, the 0.78−0.79 16 10,000 15 9,200 16 76-16-4 C 3 F 8 0.96−0.97 16 2,600 16 7,000 16 76-19-7 c-C 4 F 8 1.25−1.31 16 3,200 16 8,700 16 115-25-3 C 4 F 7 N 2.74 16 35 16 2,700 behavior of HFO4E mixed with CO 2 has also been analyzed, where a positive synergistic effect between both gases has been obtained, in addition to a less sensitive behavior toward electrical field heterogeneity (at HFO4E contents higher than 15%) 25 compared to SF 6 . However, while seeking similarity with the insulation performance of SF 6 , important aspects such as the stability of the HFO4E mixture under different conditions of use, as discussed in this study, should not be neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al . tested the compatibility of C 6 F 12 O‐N 2 mixed gas with Al and Cu at different temperatures, and found that with the increase in temperature, the corrosion degree of the copper surface deepened, promoting the decomposition of C 6 F 12 O, and the compatibility of the gas mixture with Al was greater than that of Cu [14]. Reference [15] analyzed the gas–solid compatibility relationship between environmentally friendly insulation medium C4F7N and metal copper and aluminum through density functional theory, and demonstrated the accuracy of the simulation through temperature rise experiments.…”
Section: Introductionmentioning
confidence: 99%